Effective flexural rigidity of perforated plates by means of Trefftz method with using special purpose Trefftz functions - Kołodziej, Jan A.; Mierzwiczak, Magdalena; Tylicki, Henryk (Computer Assisted Methods in Engineering and Science, 2008)
The main purpose of this paper is the investigation of the boundary effect in bending problem of perforated plates and its influence on the effective flexural rigidity. The considered strip plate is loaded by constant uniformly distributed load and has square penetration pattern. The boundary value problem for determination of deflection repeated element of structure is solved by means of boundary collocation method with a use of the special purpose Trefftz functions. These functions fulfil exactly not only governing equation but also boundary conditions on holes and some symmetry conditions. The number of perforations is discussed on effective rigidity.